2005
DOI: 10.1111/j.0906-7590.2005.04024.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecogeography of the herpetofauna of a northern California watershed: linking species patterns to landscape processes

Abstract: of the herpetofauna of a northern California watershed: linking species patterns to landscape processes. Á/ Ecography 28: 521 Á/536.Ecosystems are rapidly being altered and destabilized on a global scale, threatening native biota and compromising vital services provided to human society. We need to better understand the processes that can undermine ecosystem integrity (resistanceresilience) in order to devise strategies to ameliorate this trend. We used a herpetofaunal assemblage to first assess spatial patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 67 publications
2
48
0
Order By: Relevance
“…Increased moisture and lower more stable temperatures are associated with advancing succession in multiple forest ecosystems (Brosofske et al 1997, Chen et al 1999, Zheng et al 2000, Welsh et al 2005, Brooks and KykerSnowman 2008. This commonality in the successional process in multiple forest ecosystems would suggest that this relationship exemplifies an abiotic and biotic union, derived evolutionarily, linking late-seral forests and much of their unique constituent biota (i.e., coevolution).…”
Section: Discussionmentioning
confidence: 99%
“…Increased moisture and lower more stable temperatures are associated with advancing succession in multiple forest ecosystems (Brosofske et al 1997, Chen et al 1999, Zheng et al 2000, Welsh et al 2005, Brooks and KykerSnowman 2008. This commonality in the successional process in multiple forest ecosystems would suggest that this relationship exemplifies an abiotic and biotic union, derived evolutionarily, linking late-seral forests and much of their unique constituent biota (i.e., coevolution).…”
Section: Discussionmentioning
confidence: 99%
“…Stream salamanders such as Desmognathus spp. are thought to be good indicators of riparian and instream habitat quality (Welsh and Ollivier, 1998;Welsh et al, 2005). A small validation study (N = 10) of this approach showed positive correlations between stream salamander abundance and the Habitat FCI score (Noble et al, 2014).…”
Section: In 2010 the Us Army Corps Of Engineers Developed The Operamentioning
confidence: 99%
“…Brooks were often reduced to pools in summertime; they were crowded of amphibian life and sheltered also the three protected species against summer aridity stress. The presence of perennial streams and wetlands is recognized as an important factor for the conservation of semi-aquatic herpetofauna, especially in the arid climate of the Mediterranean area (Ficetola et al, 2004;Welsh et al, 2005), whereas inundated land is an ephemeral habitat of great value for breeding amphibian species (Helmer and Scholte, 1985;Bousbouras and Ioannidis, 1997;Brodman et al, 2003). Semi-open or open thermophilous habitats with a well developed undergrowth of low bushes such as oakwoods and heaths were the most important sites for the conservation of terrestrial herpetofauna.…”
Section: Diversity Conservationmentioning
confidence: 99%